Christ Child : cultural memories of a young Jesus - Davis, Stephen J. (Synkrisis : Comparative Approaches to Early Christianity in Greco-Roman Culture, 2014)
Little is known about the early childhood of Jesus Christ. But in the decades after his death, stories began circulating about his origins. How would early readers have made sense of this young Jesus? In this highly innovative book, Stephen Davis draws on current theories about how human communities construe the past to answer this question. He explores how ancient readers would have used texts, images, places, and other key reference points from their own social world to understand the Christ child's curious actions.